Pelatihan Metode Pembelajaran Al-Qur’an Berbasis Tilawah Untuk Meningkatan Kompetensi Guru TPQ Islahul Ummah Mamben Lauk: Training on Quranic Recitation-Based Learning Methods to Improve the Competence of Teachers at TPQ Islahul Ummah Mamben Lauk - M. Ali Karmani (Indonesia, 2025)
The low competence of TPQ teachers in reading and teaching the Qur’an in a standardized manner has affected the quality of learning at TPQ Islahul Ummah Mamben Lauk. To address this gap, the present study aims to enhance teachers’ abilities through Tilawati method training, which is systematic and easy to implement. The study employs a descriptive-quantitative approach involving 15 TPQ teachers as participants. Data were collected through observation, Qur’an reading tests, and pedagogical competency questionnaires based on Tilawati indicators, and then analyzed using descriptive techniques to identify changes in competence before and after the training. The results show a significant improvement in makhraj accuracy, tajwīd mastery, recitation fluency, and Tilawati rhythm stability. Furthermore, teachers’ pedagogical competence also increased, particularly in applying structured instructional steps and using the classical read-and-listen approach. These findings demonstrate that Tilawati training is effective in improving the quality of TPQ teachers and can serve as a model for developing Qur’an teaching competence in various basic religious education institutions.